Global issues and challenges in a changing world : psychological, cultural and group relationships - Ismail, Rosnah (Universiti Malaysia Sabah, 2009)
This edited volume is based on a collection of papers presented at the 7th Conference of the Asian Association of Social Psychology (AASP) that was organized from 25th to 28th July, 2007 at the Magellan Sutera Harbour and Resort, Kota Kinabalu, Sabah, Malaysia. The conference was meant to enhance in-depth research on Asian social psychology, its status and future directions among various Asian societies. The papers published in this volume were based on the conference theme of "Social Psycholgy: Global Issues and Challenges in a Changing World" and they were reviewed and revised before publication.